Ice : a novel - Howard, Linda, 1950- (New York : Ballantine Books, 2009)
As a brewing ice storm approaches, and despite the icy conditions that have always existed between him and Lolly Helton, combat veteran Gabriel McQueen makes the long haul to the middle of nowhere to find out whether she is safe and sound. Spotting strangers in Lolly's home--one of them packing a weapon--Gabriel rescues Lolly from her captors ... but when the escape is discovered, the heat--and the hunt--are on.
Keywords: Man-woman relationships -- Fiction; Ice storms -- Fiction; Rescues -- Fiction; Maine -- Fiction; Love stories; Suspense fiction